Altruism and egoism prosocial motivations for helping depend on relationship context - Maner, Jon K.; Gaillaiot, Mathew T. ([New York] John Wiley & Sons, Ltd, 2006)
Findings from the current study suggest that the link between helping and empathic concern?a hypothesized motivator of altruistic behavior?may be more pronounced in the context of kinship relationships than among strangers. Participants expressed their willingness to help a kin-member or stranger in specific need situations. Putative mediators of helping (empathic concern, general negative affect, perceptions of oneness) were measured. Empathic concern appeared to partially mediate effects of relationship context on willingness to help. Moreover, while controlling for egoistic motivators (negative affect, oneness), empathic concern was linked to participants' willingness to help a kin-member but not a stranger. Findings suggest that factors motivating prosocial action in close relationships may be different from those that motivate helping among strangers.
Includes bibliographical references.
Keywords: Altruism; Empathy; Egoism; Family